Jesus the Jew in Christian memory : theological and philosophical explorations - Meyer, Barbara 1968- (Cambridge University Press, 2020)
Jesus the Jew is the primary signifier of Christianity's indebtedness to Judaism. This connection is both historical and continuous. In this book, Barbara Meyer shows how Christian memory, as largely intertwined with Jewish memory, provides a framework to examine the theological dimensions of historical Jesus research. She explores the topics that are central to the Jewishness of Jesus, such as the Christian relationship to law, and otherness as a Christological category. Through the lenses of the otherness of the Jewish Jesus for contemporary Christians, she also discusses circumcision, natality, vulnerability, and suffering in dialogue with thinkers seldom drawn into Jewish-Christian discourse, notably Hannah Arendt, Julia Kristeva, Martha Nussbaum and Adi Ophir. Meyer demonstrates how the memory of Jesus' Jewishness is a key to reconfiguring contemporary challenges to Christian thought, such as particularity and otherness, law and ethics after the Shoah, human responsibility, and divine vulnerability